SPECIFIC TECHNOLOGIES OF RURAL (AGRICULTURAL) TOURISM IN THE REPUBLIC OF TATARSTAN - N. N. Ermolayeva (Russian Journal of Economics and Law)
The article views the important components of rural (agricultural) tourism, shows the interconnection with other kinds of tourism, studies the tourist motivations, and underlines the importance of delivering complex agrotourism services. The author also studies the influence of season factor on rural tourism development in the Republic of Tatarstan, summarizes the foreign and domestic experience, and gives recommendations for developing the priority directions of tourism in the Republic.